A new MR-SAD algorithm for the automatic building of protein models from low-resolution X-ray data and a poor starting model. (2018) - Skubak, Pavol; Arac, Demet; Bowler, Matthew W.; Correia, Ana R.; Hoelz, Andre; Larsen, Sine
No abstract available